Exploring the Potentials of Phytochemicals for Targeting Coronavirus - Khanna, Shirin; Ganesan, Aravindhan; Kalyaanamoorthy, Subha (Natural Products Journal, The, 2022)
Since the initial outbreak in December 2019, the COVID-19 pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to more than 3 million deaths worldwide. There is an urgent need for developing a potential therapy against SARS-CoV-2. Exploring the potentials of phytochemicals towards inhibition of SARS-CoV-2 proteins remains of significant scientific interest. The therapeutic values of phytochemicals in the treatment of diseases, such as viral infections, are known for a long time. In this review, we present a brief overview of the past experimental and computational efforts on evaluating phytochemicals against SARS coronaviruses, an earlier coronavirus strain. We discuss natural metabolites of different structural and chemical scaffolds, including polyphenols, flavonoids, and phytosterols, which can be promising compounds for screening against the currently evolving SARS-CoV-2 virus.
Keywords: Coronavirus